Pilot-scale comparison of microfiltration/reverse osmosis and ozone/biological activated carbon with UV/hydrogen peroxide or UV/free chlorine AOP treatment for controlling disinfection byproducts during wastewater reuse. (1st April 2019) - Chuang, Yi-Hsueh; Szczuka, Aleksandra; Shabani, Farzaneh; Munoz, Joline; Aflaki, Roshanak; Hammond, Slavica D.; Mitch, William A.
Abstract: Ozone and biological activated carbon (O3 /BAC) is being considered as an alternative advanced treatment process to microfiltration and reverse osmosis (MF/RO) for the potable reuse of municipal wastewater. Similarly, the UV/free chlorine (UV/HOCl) advanced oxidation process (AOP) is being considered as an alternative to the UV/hydrogen peroxide (UV/H2 O2 ) AOP. This study compared the performance of these alternative treatment processes for controlling N -nitrosamines and chloramine-reactive N -nitrosamine and halogenated disinfection byproduct (DBP) precursors during parallel, pilot-scale treatment of tertiary municipal wastewater effluent. O3 /BAC outperformed MF/RO for controlling N -nitrosodimethylamine (NDMA), while MF/RO was more effective for controlling N -nitrosomorpholine (NMOR) and chloramine-reactive NDMA precursors. The UV/H2 O2 and UV/HOCl AOPs were equally effective for controlling N -nitrosamines in O3 /BAC effluent, but UV/HOCl was less effective for controlling NDMA in MF/RO effluent, likely due to the promotion of dichloramine under these conditions. MF/RO was more effective than O3 /BAC for controlling chloramine-reactive halogenated DBP precursors on both a mass and toxicity-weighted basis. UV/H2 O2 AOP treatment was more effective at controlling the toxicity-weighted chloramine-reactive DBP precursors for most halogenated DBP classes by preferentially degrading the more toxic brominated species. However, the total toxicity-weighted DBP precursor concentrations were similar for treatment by either AOP because UV/H2 O2 AOP treatment promoted the formation of iodoacetic acid, which exhibits a very high toxic potency. The combined O3 /BAC/MF/RO train was the most effective for controlling N -nitrosamines and the total toxicity-weighted DBP precursor concentrations with or without treatment by either AOP. Graphical abstract: Image 1 Highlights: O3 /BAC outperformed MF/RO for controlling NDMA. MF/RO outperformed O3 /BAC for controlling NMOR. MF/RO was more effective for controlling total toxicity-weighted DBPs. The UV/HOCl AOP was less effective for controlling NDMA in RO permeate. The UV/H2 O2 AOP better controlled total toxicity-weighted DBPs except iodoacetic acid.